Individual Taxpayer Compliance: The Influence of Tax Socialization, the Self-assessment System, and Law Enforcement - Rahel Oselbi; Agustiawan Agustiawan; Rudi Syaf Putra (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study examines the influence of tax socialization, the self-assessment system, and law enforcement on individual taxpayer compliance. The research adopts a quantitative approach. The population consists of 175,220 individual taxpayers registered at the Senapelan Primary Tax Office in 2023. A sample of 400 registered individual taxpayers was selected using accidental sampling. Primary data were collected through structured questionnaires and analyzed using multiple linear regression. The results indicate that tax socialization, the implementation of the self-assessment system, and law enforcement significantly affect individual taxpayer compliance. The self-assessment system and consistent law enforcement emerge as dominant factors in encouraging compliant behavior, indicating that clarity of procedures and firm regulatory enforcement strengthen taxpayers’ willingness to fulfill their obligations. In addition, effective tax socialization contributes to improving taxpayers’ understanding and awareness, which supports voluntary compliance. These findings suggest that enhancing taxpayer compliance requires an integrated approach that combines continuous education, transparent administrative systems, and consistent enforcement mechanisms. Strengthening these aspects can promote sustainable compliance among individual taxpayers.